Hardware and software: verification and testing 5th International Haifa Verification Conference, HVC 2009, Haifa, Israel, October 19-22, 2009, revised selected papers - Namjoshi, Kedar S.; Zeller, Andreas; Ziv, Avi (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post proceedings of the 5th International Haifa Verification Conference, HVC 2009, held in Haifa, Israel in October 2009. The 11 revised full papers presented together with four abstracts of invited lectures were carefully reviewed and selected from 23 submissions. The papers address all current issues, challenges and future directions of verification for hardware, software, and hybrid systems and present academic research in the verification of systems, generally divided into two paradigms - formal verification and dynamic verification (testing).